2016
DOI: 10.17795/mejrh-40247
|View full text |Cite
|
Sign up to set email alerts
|

Age and Comorbidities Affect Quality of Life in Patients With Osteoarthrtitis and Knee Replacement

Abstract: Background: Osteoarthritis (OA) is a multifactorial, disabling and degenerative disease that worsens with age and affects patient's health-related quality of life (HRQOL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The osteoarthritis research society international has suggested non-pharmacological, pharmacological, and surgical recommendations for the treatment/management of knee OA (2). Total knee arthroplasty is the last alternative in advanced knee OA patients, and although it is an invasive and expensive procedure with a 95% rate of survival at 10 years, it might have complications (4,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…The osteoarthritis research society international has suggested non-pharmacological, pharmacological, and surgical recommendations for the treatment/management of knee OA (2). Total knee arthroplasty is the last alternative in advanced knee OA patients, and although it is an invasive and expensive procedure with a 95% rate of survival at 10 years, it might have complications (4,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…39,42,43 Forogh et al 19 sustain that some studies have reported an inverse relationship between age and response to treatment; in younger patients the outcome was better than those over 50 years. 44 Fernández-Cuadros et al have stated that age is related to knee OA severity and outcomes are dependent on such variable. 3,44 There is only one study that shows benefit on older patients with even 3º grade knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…44 Fernández-Cuadros et al have stated that age is related to knee OA severity and outcomes are dependent on such variable. 3,44 There is only one study that shows benefit on older patients with even 3º grade knee OA. 41 Our present study shows a clear correlation between age and knee severity and for the first time shows statistical significant improvement of PRP-protocol treatment in all K-L grades, even 4º grade, to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities are defined as diseases or medical conditions which do not relate causally to the primary diagnosis but coexist with it. Elderly patients generally have more comorbidities but the effects of comorbidities on the results of arthroplasty need to be further studied (3). In a medical environment, classifying comorbidities using valuebased metrics can help improve pre-surgical counseling, decrease potential complications and allow for perioperative resources to be properly assigned.…”
Section: Introductionmentioning
confidence: 99%